Formação continuada sobre pregão eletrônico para profissionais que atuam na gestão da educação profissional e tecnológica - Santa Bárbara, Antônio José (2025)
The main objective of this research was to analyze the contributions of an online continuing education course on electronic bidding aimed at professionals who work in the management of Professional and Technological Education. In addition to specifically reflecting on the diagnosis of the need for continuing education of professionals (or not) who work in the management of Professional and Technological Education at Ifal – Campus Maceió, identify the advantages and disadvantages of applying a course on electronic bidding in Professional and Technological Education and evaluate the possibility of applying the course in the format of an extension course. The theoretical basis presented a brief history of the initial milestones and some references regarding Professional and Technological Education and made considerations about management in Professional and Technological Education, emphasizing both the importance of training people and the theories of Andragogy in the context of the adult teaching and learning process, in addition to the recognition of Administrative Technicians in Education, having as a basis for the formatting of the Educational Product the Theory of Significant Learning by David Paul Ausubel, concomitantly with the three thematic axes of Gabriel Kaplún and the content typologies presented by Antoni Zabala. To achieve the objectives, a qualitative research methodology was adopted, of the action research type, organized in the following stages: (1) exploratory; (2) diagnostic; (3) elaboration of the Educational Product online continuing education course on electronic bidding; (4) application of the Educational Product; (5) evaluation and validation of the Educational Product. The data collection instruments were document analysis and online questionnaires for diagnosis and evaluation of the Educational Product. The data were analyzed using Laurence Bardin's content analysis technique in three fundamental phases: pre-analysis; exploration of the material and treatment of the results. The results achieved with this research were the construction of an Educational Product of the online continuing education course type that contributed to the training of professionals in the sphere of electronic bidding. In addition, it was identified that the course could be used as an extension course for the training of people who are not employees of the Institution.